Three in one measurement tool for voltage, current and speed / Muhammad Ismail Husaini - Husaini, Muhammad Ismail (2024)
The goal of this project is to address the limitations of existing measurement tools using microcontrollers by developing a multi measurement tool using Arduino as the microcontroller. The tool will combine the capabilities of a voltmeter and ammeter into a single device, providing users with a more efficient and user-friendly solution. Additionally, a speed sensor will be integrated into the tool, enabling the measurement of speed in electrical appliances such as induction motors and DC motors. By combining multiple measurement features into one device, the project seeks to create a versatile three-in-one tool for electrical measurements. A successful implementation of the voltage sensor, current sensor, and speed sensor is what is expected from this project, with the Arduino UNO serving as the system's primary controller. Overall, the project aims to achieve its objectives and provide a comprehensive solution for electrical measurement needs.